ANTHOCYANIN FROM BEGONIA CULTIVARS AND ITS ANTIOXIDANT POTENTIALITIES - ASWATHY JM; DINESH BABU KV; MURUGAN K (International Journal of Pharma and Bio Sciences, 2016)
Plant based antioxidants from fruits, vegetables and flowers have fascinated pharmaceutical industries. Anthocyanins are proven nutraceutical health. Begonia species forms diverse hyper group and are distinguished on the basis of morphological parameters. Begonia rex-cultorum (Baby rainbow) and Begonia malabarica exhibited the highest antioxidant activities. The anthocyanin concentration positively correlates with the antioxidant potentialities among the cultivars. The IC50 value related with DPPH and metal chelating activities of the B. rex-cultorum (Baby rainbow) extract are 32.3 µg/mL and 18.7 µg/mL respectively. Remarkable scavenging potentialities are displayed against metal chelating, β-carotene bleaching, ABTS radical, FRAP assays and the results are comparable with synthetic antioxidant like BHT. The diversity in radical scavenging in these assays may be due to factors like stereo selectivity of the radicals or due to the differential solubility of anthocyanin molecules in the crude extract. Further studies are warranted to isolate and fractionate the major anthocyanins in the cultivars.